Historical, Philosophical And Psychological Dimensions Of Bilingualism: Cognitive And Neurological Perspectives - Hee, Alvina Chee Ying; Lee, Brice Tseen Fu (Academic Journal of Psychology and Counseling, 2025)
Research on bilingualism has traditionally focused on its effects on language proficiency, yet a significant gap exists in understanding its broader cognitive impacts, particularly regarding executive functions and brain structure. This study aimed to bridge that gap by examining the multifaceted influences of bilingualism on cognitive function, incorporating historical and philosophical perspectives to provide a comprehensive analysis. Using a systematic literature review approach, supported by neuroimaging studies, this research explored how bilingualism enhances brain plasticity and executive functions, such as attentional control and task-switching. Historical analysis reveals the shift from early 20th-century deficit views of bilingualism to the recognition of its cognitive advantages. Philosophical discussions further contextualize these findings, addressing the ethical considerations of cognitive enhancement and the mind-brain relationship in bilingual contexts. The results suggest that bilingualism confers distinct cognitive benefits, reshaping both brain structures and functions. Based on these findings, this study offers key recommendations for improving future research methodologies, emphasizing the need for more diverse and standardized studies, and suggests practical counseling approaches that account for the psychological and philosophical complexities of bilingual identity. These insights challenge traditional views on cognitive development and have significant implications for educational policies, counseling strategies, and future neuroscience research.